2013
DOI: 10.1530/eje-13-0170
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of matrix metalloproteinase-3 in the pathogenesis of macroprolactinaemia in some patients with rheumatoid arthritis

Abstract: Objective: Macroprolactin primarily comprises a complex of prolactin (PRL) and IgG molecules, particularly anti-PRL autoantibodies. However, it is unknown why autoantibodies against PRL develop in certain subjects. This study aimed to elucidate post-translational modifications in the PRL molecule that may be involved in the pathogenesis of macroprolactinaemia. Methods: Macroprolactinaemia was screened with a polyethylene glycol method in 238 patients with rheumatoid arthritis (RA) and 302 control subjects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, few studies have suggested increased occurrence of macroprolactinemia with age. 19 Also underlying etiology or the reason for testing for hyperprolactinemia was not a factor on the occurrence of macroprolactinemia. Macroprolactinemia in India Sharma et al…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have suggested increased occurrence of macroprolactinemia with age. 19 Also underlying etiology or the reason for testing for hyperprolactinemia was not a factor on the occurrence of macroprolactinemia. Macroprolactinemia in India Sharma et al…”
Section: Discussionmentioning
confidence: 99%
“…There was also no correlation between IL-21 and anti-TPO and anti-TG levels (Table 3). Systematic lupus erythematosus and RA as autoimmune diseases with an increased prevalence of serum autoantibodies were associated with macroprolactinaemia (5,6). There are also some studies showing significantly higher prolactin levels in HT patients rather than controls (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of prolactin to an immunoglobulin forms macroprolactin and is usually formed by IgG antibody. Macroprolactinaemia has been found to be associated with different autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis in different studies (5)(6).…”
Section: Introductionmentioning
confidence: 99%